When fairies go bad - Vernon, Ursula (New York : Dial Books for Young Readers, 2012)
Danny's mother has disappeared into a fairy ring growing in her backyard vegetable garden, and Danny and his friends, Wendell and Christiana, must go to Faerie to try to save her.
Keywords: Adventure and adventurers -- Fiction; Fairies -- Fiction; Dragons -- Fiction; Iguanas -- Fiction; Humorous stories